The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3390/cancers13143640
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Metastatic Uveal Melanoma Prognostic Score (MUMPS) for Use in Patients Receiving Immune Checkpoint Inhibitors

Abstract: Metastatic uveal melanoma (mUM) is a rare disease. There are limited data on prognostic clinical factors for overall survival (OS) in patients with mUM treated with immune checkpoint inhibitors (ICI). Retrospective and non-randomized prospective studies have reported response rates of 0–17% for anti-PD1/L1 ± anti-CTLA4 ICI in mUM, indicating a potential benefit only in a subset of patients. This study evaluates the characteristics associated with ICI benefit in patients with mUM. We performed a single-center r… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 47 publications
(58 reference statements)
0
8
0
Order By: Relevance
“…A prognostic score for patients with MUM, including the variables time to metastatic diagnosis, presence of bone metastases, and LDH, was recently developed [ 41 , 42 , 43 ]. Based on the results of our analysis, the parameters age (cut-off: ≥55 years), as well as LDH, S100, and NLR (cut-off: 3.5), should be considered in case of prognosis assessment.…”
Section: Discussionmentioning
confidence: 99%
“…A prognostic score for patients with MUM, including the variables time to metastatic diagnosis, presence of bone metastases, and LDH, was recently developed [ 41 , 42 , 43 ]. Based on the results of our analysis, the parameters age (cut-off: ≥55 years), as well as LDH, S100, and NLR (cut-off: 3.5), should be considered in case of prognosis assessment.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the demographic characteristics of patients differed between those receiving monotherapy and those with combination therapy. Among patients receiving single-agent anti-PD-1/L1, 54% were 65 years or older, whereas this proportion in those receiving anti-PD-1 + anti-CTLA-4 was 33%, which may reflect a drug selection bias by oncologists in this center [ 44 ]. Overall, the conclusions of these retrospective studies on the effect of dual-agent ICIs are somewhat controversial, and none are sufficiently convincing due to their small samples.…”
Section: Current Status Of Clinical Studies Regarding Icis In Patient...mentioning
confidence: 99%
“…Thus, for patients with MUM who lack options, ICIs are worthy of consideration. Although there has not been a definite biomarker of prognostication for ICIs in MUM, several studies agreed that the lactate dehydrogenase (LDH) level is associated with ICI treatment response [ 34 , 37 , 44 ]. The low LDH values potentially indicate the benefit of treatment of ICIs in MUM [ 49 ].…”
Section: Current Status Of Clinical Studies Regarding Icis In Patient...mentioning
confidence: 99%
“…Mounting evidence points towards a unique biological behaviour in UM, with infiltration by immune cells strongly linked with a tumour growth stimulatory effect, instead of a tumour suppressing effect, which is normally present in other types of neoplasias [ 272 , 311 , 329 ]. In addition, unlike in cutaneous melanoma, immune checkpoint inhibition has not yielded meaningful results for the majority of UM patients [ 123 , 330 , 331 ]. Together, these results highlight the presence of a strongly immunosuppressive microenvironment in primary UM, and our knowledge on this distinctive phenomenon remains in its infancy [ 329 , 332 , 333 ].…”
Section: Current Challenges and Future Perspectives In Uveal Melanomamentioning
confidence: 99%
“…Interestingly, an association between BAP1 loss and the infiltration of the tumoural microenvironment by lymphocytes and macrophages, with concomitant overexpression of genes involved in immunosuppression has been established [ 332 ]. Classically and well-established checkpoint inhibitor molecules such as CTLA4 and PD-1 seem to be relevant only for limited subsets of UM patients [ 123 , 330 , 331 ]. On the other hand, a recent study involving single cell RNA sequencing demonstrated that an emerging checkpoint inhibitor molecule, lymphocyte-activation gene-3 (LAG3), is expressed at high levels in most of T-CD8+ cytotoxic UM TILs [ 334 ].…”
Section: Current Challenges and Future Perspectives In Uveal Melanomamentioning
confidence: 99%